Situational Leadership in the Era of Independent Learning: Strategies for Improving Educational Quality - Safrida, Usma Riza; Usman, Nasir; Bahrun, Bahrun (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study explores the application of situational leadership by principals in improving the quality of education in public senior high schools. This study is based on the importance of situational leadership in facing educational challenges, especially in improving the quality of teaching and supporting teacher professional development in the Merdeka Belajar era. The qualitative research method with a multi-site study type examines two different educational locations to compare situational leadership's implementation. Data were analyzed using the Miles and Huberman analysis approach, which includes data reduction, data presentation, and conclusion. The study's findings indicate that principals apply situational leadership that is flexible and responsive to the needs and readiness of teachers. Principals use more directive and supportive leadership styles and give more freedom to experienced teachers. Applying this leadership style has been shown to increase motivation and quality of teaching and encourage continuous teacher professional development. Situational leadership based on the perspective of Hersey and Blanchard's theory can improve the quality of education. This study is expected to provide a deeper understanding of the importance of implementing situational leadership in Indonesian education. It suggests that other schools adjust their leadership style according to the needs and readiness of individuals to improve the quality of education effectively.